A systematic review on exploring the influence of Industry 4.0 technologies to enhance supply chain visibility and operational efficiency - Tahsina Khan; Md Mehedi Hasan Emon; Md Adnan Rahman (Review of Business and Economics Studies)
This systematic review investigates the implications of Industry 4.0 technologies on supply chain visibility and operational efficiency. The primary aim is to discern the impact of technological integration on contemporary supply chain dynamics. Methods: A comprehensive search strategy identified 65 pertinent studies published between 2015 and 2023. The review adheres to systematic methodologies, employing the Critical Appraisal Skills Programme framework for quality assessment. Data synthesis incorporates qualitative and quantitative analyses to distill key themes and patterns. Results: The review unveils the pivotal role of information visibility in fortifying supply chain outcomes, emphasizing the need for a dual investment strategy encompassing technological solutions and a collaborative organizational culture. Regional variations in supply chain practices, insights from humanitarian supply chains, and the influence of environmental factors on agility broaden the understanding of Industry 4.0 implications. Organizations are urged to adopt a context-specific, adaptive approach, recognizing the significance of intangible assets and tailoring strategies to local contexts for optimal supply chain performance. This systematic review contributes a nuanced understanding of Industry 4.0’s transformative potential in supply chain management, emphasizing the interplay between technology, organizational culture, and regional contexts.